2009
DOI: 10.1016/j.marenvres.2008.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Benthic fluxes of copper, complexing ligands and thiol compounds in shallow lagoon waters

Abstract: a b s t r a c tBenthic fluxes of copper, copper complexing ligands and thiol compounds in the shallow waters of Venice Lagoon (Italy) were determined using benthic chambers and compared to porewater concentrations to confirm their origin. Benthic copper fluxes were small due to small concentration differences between the porewaters and the overlying water, and the equilibrium concentration was the same at both sites, suggesting that the sediments acted to buffer the copper concentration. Thiol fluxes were $10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 49 publications
4
15
0
Order By: Relevance
“…In this study, the speciation analysis showed that the highaffinity organic ligands bound > 99.9% of the dissolved Cu, effectively buffering the system against small changes in dissolved Cu concentrations, and controlled the free Cu 21 concentrations well below the possible toxicity threshold (approximately being 10 211 mol L 21 based on Moffett et al [1997], Brand et al [1986], and Sunda et al [1987]). This is similar to what has been observed worldwide in coastal seawater or the open ocean [Buck et al, 2007;Chapman et al, 2009].…”
Section: Cu Speciationsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the speciation analysis showed that the highaffinity organic ligands bound > 99.9% of the dissolved Cu, effectively buffering the system against small changes in dissolved Cu concentrations, and controlled the free Cu 21 concentrations well below the possible toxicity threshold (approximately being 10 211 mol L 21 based on Moffett et al [1997], Brand et al [1986], and Sunda et al [1987]). This is similar to what has been observed worldwide in coastal seawater or the open ocean [Buck et al, 2007;Chapman et al, 2009].…”
Section: Cu Speciationsupporting
confidence: 90%
“…[]). This is similar to what has been observed worldwide in coastal seawater or the open ocean [ Buck et al ., ; Chapman et al ., ].…”
Section: Resultsmentioning
confidence: 96%
“…This suggests that as well as a freshwater source, L 1 is both produced and utilized along the estuary and, as a result, local concentrations may vary seasonally. This is consistent with the identification of L 1 as a thiol-type species, since sediment and pore waters are likely sources of thiols (Kiene et al, 1990;Zhang et al, 2004), which have been shown to diffuse out of sediments in similar shallow water marshes (Chapman et al, 2009).…”
Section: Seasonality In the Datasupporting
confidence: 86%
“…Synechococcus are the second most abundant bacterioplankton fraction in waters offshore of the Duplin River in summer . As well as water column sources for ligands, likely sources of thiols are benthic microbes and sulfur-containing amino acids within the sediment (Kiene et al, 1990;Chapman et al, 2009), whilst the humics in this type of environment are likely products of relatively recent degradation of local plant matter (Averett et al, 1994) such as fungal breakdown of lignocellulose (Newell, 2001;Buchan et al, 2003). Spartina alterniflora and many of the higher plants in the marsh also release dimethylsulfoniopropionate (DMSP) (Bacic et al, 1998;Kiehn and Morris, 2010), which can add be an additional source of thiols.…”
Section: Possible Sources Of the Ligandsmentioning
confidence: 99%
“…[a] Signal to noise ratio ( SNR ) of 3 [43] These effects can be related to the different interactions of the metal ions with the bulk modifier. The stability constants of metal complexes with sulfur and nitrogen reported in the literature [39][40][41][42], show that cadmium is the least stable (lg K ¼ 4.6), the stability of copper (lg K ¼ 12.5) and lead (lg K ¼ 12.1) are almost equal and mercury (lg K ¼ 18.8) is more stable. The results in Table 4 showed that cadmium suffered more interference when the concentration of the other species changed, that can be ascribed to the fact that cadmium has a lower stability constant than the other metals.…”
mentioning
confidence: 99%